Prevalence of Intestinal Parasitic Infections Among Diarrheic Patients from Ahvaz, Southwestern Iran - Karami, Saina; Beiromvand, Molouk; Kohansal, Kobra (Infectious Disorders - Drug Targets, 2021)
Background: Intestinal parasitic infections are among the most common infections in humans, particularly in resource-poor communities. Gastrointestinal parasites, specially protozoa, can lead to diarrhea, malabsorption, and anemia. The majority of parasitic diarrhea is caused by Entamoeba histolytica, Giardia duodenalis, and Cryptosporidium spp. The present study aimed to evaluate the prevalence of intestinal parasites among diarrheic patients referred to the Shahid Rajaee Polyclinic, Ahvaz, southwestern Iran. Methods: A cross-sectional study was conducted to determine the prevalence of intestinal parasites among 250 diarrheic patients using direct smear, formalin-ether concentration, Ziehl-Neelsen and trichrome staining. Results: The results indicated that 34.4% (86/250) of the patients were infected with pathogenic parasites. Giardia duodenalis with an occurrence of 18.8% (47/250) and Cryptosporidium spp. with a frequency of 2.8% (7/250) had the highest and lowest infection rates, respectively. Blastocystis hominis with a frequency of 15.2% (38/250) showed the highest prevalence rate after G. duodenalis. Entamoeba histolytica/dispar was observed in 3 (1.2%) of diarrheic patients. The age group 1−10 years old was the most frequently infected group (27.9%). We could not find a significant association between the source of drinking water and intestinal parasitic infections (p= 0.912). Conclusion: This study demonstrated that G. duodenalis was the predominant parasite found among the patients. The results revealed that intestinal parasites were one of the main health problems in the region.
Keywords: Cryptosporidium